New exact soliton wave solutions appear in optical fibers with Sardar sub equation and new auxiliary equation techniques - Umair Asghar; Muhammad Imran Asjad; Yasser Salah Hamed; Ali Akgul; Murad Khan Hassani (Scientific Reports)
Abstract This paper comprehensively analyzes exact solutions for the nonlinear long-short wave interaction system within the optical field. Consider two general techniques in this field, the Sardar sub-equation method, and a new auxiliary-equation technique. These methods are applied to derive a wide range of soliton solutions for nonlinear partial differential equations. By transforming the original partial differential equation into an ordinary differential equation using an appropriate transformation, various types of solitary wave solutions are obtained. The novelty of this work lies in the application of two powerful analytical methods. The study significantly broadens the scope of these techniques and their applications, providing a diverse set of exact solutions. To enhance comprehension, the obtained solutions are visualized through 3D, 2D, contour, and density plots, offering clear insights into the dynamics of solitary waves. Long-short-wave interaction model has many applications in different kinds of areas such as in optical fiber communication, to understand the interaction between different wave components that can influence the transmission of signals. This model is used to study the interaction between ion-acoustic waves and electron plasma waves. This helps in understanding energy transfer and wave stability in plasma, which is essential for applications like fusion energy research and space plasma. This is important in coastal engineering for predicting wave behaviors that affect coastal structures, sediment transport, and tsunami dynamics.